2019
DOI: 10.1016/j.crad.2018.11.012
|View full text |Cite|
|
Sign up to set email alerts
|

The National Institute for Health Research: making an impact in imaging research

Abstract: Since the inception of the National Institute for Health Research (NIHR) in 2006, the landscape for the delivery of clinical research within the NHS has been transformed. Clinical Radiology has benefitted from funding opportunities for primary imaging research as well as improvements to the supporting research infrastructure to provide imaging for many clinical trials. However, in an increasingly challenging NHS environment, the NIHR and Clinical Radiology have to evolve an effective working partnership to ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The commercial value can itself take a range of forms, including monetary, intellectual property (IP) ownership, and equity and royalties from any products developed, all of which can be achieved via payment or in the form of beneficial access terms for the NHS. 50 It is important to create the right frameworks to identify and realise the benefits for patients and the NHS where data underpins innovation, with an increasing focus on establishing a new 'social contract' to achieve this. 51 Due to the severity of the COVID-19 pandemic, the NCCID has established a contractual arrangement with approved data users whereby data is provided to the user free of charge, but any related technologies developed as a result of this must be provided at zero-licence fee cost to the NHS for the duration of the Data Access Agreement signed by the data user.…”
Section: Patient and Public Engagement: Consulting Patients And The Wider Public On The Requirements And Benefits Of Algorithmic Developmmentioning
confidence: 99%
“…The commercial value can itself take a range of forms, including monetary, intellectual property (IP) ownership, and equity and royalties from any products developed, all of which can be achieved via payment or in the form of beneficial access terms for the NHS. 50 It is important to create the right frameworks to identify and realise the benefits for patients and the NHS where data underpins innovation, with an increasing focus on establishing a new 'social contract' to achieve this. 51 Due to the severity of the COVID-19 pandemic, the NCCID has established a contractual arrangement with approved data users whereby data is provided to the user free of charge, but any related technologies developed as a result of this must be provided at zero-licence fee cost to the NHS for the duration of the Data Access Agreement signed by the data user.…”
Section: Patient and Public Engagement: Consulting Patients And The Wider Public On The Requirements And Benefits Of Algorithmic Developmmentioning
confidence: 99%
“…6,7 Without the time to engage with and evaluate new diagnostic and treatment strategies, the NHS will fall behind other service providers in evidence-based healthcare, particularly in the most technologically driven specialties, such as clinical radiology. 8 The current inadequate level of SPA time has directly contributed to a distinct lack of research involvement and leadership, as well as an inconsistent approach to quality improvement and education, at a time when advances in imaging methodology and delivery are becoming even more critical to healthcare improvements. Although there will naturally be less research capacity in the most clinically under-resourced specialties, we are particularly concerned that over half the respondents were not involved in research in any capacity over the last year, and only 10% of non-academics reported spending more than an hour each week on research.…”
Section: Commentarymentioning
confidence: 99%
“…The work of the NIHR Imaging project and NIHR Clinical Research Network imaging steering group, led by Professor Steve Smye, is a start but still a "drop in the ocean". 8 Only through high-level strategic support from all funding bodies and actively looking to promote imaging-led activities, either through infrastructure support, consultant time or scanner time, will this be tackled in the short term. Investment now will help to identify and develop high-impact research projects that will reap future rewards.…”
Section: Commentarymentioning
confidence: 99%